2022
DOI: 10.1159/000525277
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of HPVs, EBV, and MMTV-Like Virus in Breast Cancer in Qatar

Abstract: Introduction: Human papillomaviruses (HPVs), Epstein-Barr virus (EBV), and mouse mammary tumor virus-like virus (MMTV-like virus) can be present and contribute to breast cancer development and progression. However, the role of these oncoviruses and their crosstalk in breast cancer is still unclear. Methods: We explored the co-presence of high-risk HPVs, EBV, and MMTV-like virus in 74 breast cancer samples from Qatar using PCR. Results: We found the presence of HPV and EBV in 65% and 49% of our cancer sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The current meta-analysis confirms the wide variations existing among the included studies. Various reasons have been described for the aforementioned discrepancy, which not only affects the possibility of an association of HPV with BC, but also the distribution of the HPV genotypes: Geographic region(s) of the samples, genetic background, cultural variations such as variable sexual practices and patterns, sample types such as fresh versus FFPE samples, age of the selected populations, sensitivity of the detection methods used, condition of the preserved samples that can hamper DNA quality, the histological type of BCs (IDC versus ductal adenocarcinoma in situ), the absence of an international standard assay for HPV genotyping and the unintentional contamination of samples with the genome of other potentially oncogenic viruses, such as EBV, MMTV, CMV and HSV (2,4,7,13,31,(94)(95)(96)(97)(98).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current meta-analysis confirms the wide variations existing among the included studies. Various reasons have been described for the aforementioned discrepancy, which not only affects the possibility of an association of HPV with BC, but also the distribution of the HPV genotypes: Geographic region(s) of the samples, genetic background, cultural variations such as variable sexual practices and patterns, sample types such as fresh versus FFPE samples, age of the selected populations, sensitivity of the detection methods used, condition of the preserved samples that can hamper DNA quality, the histological type of BCs (IDC versus ductal adenocarcinoma in situ), the absence of an international standard assay for HPV genotyping and the unintentional contamination of samples with the genome of other potentially oncogenic viruses, such as EBV, MMTV, CMV and HSV (2,4,7,13,31,(94)(95)(96)(97)(98).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the commercial kits used for DNA extraction and amplification by PCR, as well as the specific type of PCR used in every study, nested or quantitative PCR, differed among the included studies. Furthermore, it is considered a challenge to completely eliminate the possibility of specimen contamination with other oncogenic viruses, such as EBV ( 10 ), which could lead to carcinogenesis caused by these viruses and not by HPV ( 98 ). Moreover, the low viral loads detected in breast specimens impede the identification of HPV DNA in patients with BC ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors [ 25 , 100 , 102 , 108 , 123 ] failed to report any statistical association between MMTV-like virus and clinicopathological characteristics of breast cancer. Hachana et al [ 115 ] reported an inverse correlation between MMTV presence and progesterone receptor and HER2 status.…”
Section: Mmtvmentioning
confidence: 99%
“…Arab BC rates vary per region. Saudi Arabia had 22 BC cases per 100,000 women, the UAE 23, Kuwait, Jordan, and Qatar 40, and Bahrain 53 [3]. Saudi Arabia has a higher BC rate, particularly in younger women, than in western nations [4].…”
Section: Introductionmentioning
confidence: 99%